GAYA HIDUP PEREMPUAN PEMINUM ALKOHOL DI KOTA PEKANBARU - Wewen Sarmita; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Alcohol is considered as a lifestyle that requires them to make the drink as values and rules of the association itself, not only that, alcohol is also a lifestyle that demands women who are involved in work that is usually done in entertainment venues, one of which is women workers night which is demanded to drink alcohol and accompany its customers in a club or entertainment place that tends to sell liquor .. Informants who have been interviewed numbered five people namely the initials VC, MG, SR, SR, VR and BL. All five of them work as women workers at night entertainment venues and then with all the factors demanding that they have to drink alcohol so that it is now a habit or lifestyle. The lifestyle of informants as alcohol drinkers is marked by the first (activity) of daily informants who work in nightclubs every day, second (interest) informants about alcohol, the type of alcohol they like is usually diverse, some are bottled and mixed, third (opinions) informants about alcohol, according to them alcohol can bring pleasure, happiness even if only for a moment, this interesting phenomenon the author to make a discussion about the lifestyle of women who drink alcohol and what factors affect women drink alcohol in the city of Pekanbaru and then subsequently formulated in the title "Lifestyle of Women Drinking Alcohol in Pekanbaru City." Keywords: Women’s, Lifestyle, Alcohol